2008
DOI: 10.2139/ssrn.2322283
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation of Human Capital Disclosure from the Resource Based Perspective

Abstract: Though the importance of human capital (HC) in firm value creation is firmly established in the literature the level of emphasis placed on human capital disclosure (HCD) by preparers of financial statements and sell-side analysts is minimal. The purpose of this paper is to address this dilemma by critically analysing the conceptualisation of human capital in disclosure literature and introduce a more germane explanation. Keywords AbstractPurpose -Though the importance of human capital (HC) in firm value creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…In CSR report the ICVD, compared with ICVD in annual report, gives a broader and more transparency view of the company value creation process because the disclosure is more balanced between human and relational capital (Abeysekera, 2006). Differently from previous annual report research (Abhayawansa and Abeysekera, 2008) human capital is the most reported category and it is viewed as an asset that the companies try to manage and engage through disclosure and a clear and consistent communication process to built mutual trust and good relationship. Regard the high frequency of human capital Perrini (2006) asserts that human capital relationship is an essential topic of CSR reporting because employees are one of the primary company stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…In CSR report the ICVD, compared with ICVD in annual report, gives a broader and more transparency view of the company value creation process because the disclosure is more balanced between human and relational capital (Abeysekera, 2006). Differently from previous annual report research (Abhayawansa and Abeysekera, 2008) human capital is the most reported category and it is viewed as an asset that the companies try to manage and engage through disclosure and a clear and consistent communication process to built mutual trust and good relationship. Regard the high frequency of human capital Perrini (2006) asserts that human capital relationship is an essential topic of CSR reporting because employees are one of the primary company stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Mccann (2016) found that HC experts cannot predict the effect of disclosure in providing value to the investors unless it is disclosed in detail. Due to these reasons, HC is the least reported in corporate annual reports in Italy (Bozzolan, Favotto & Ricceri, 2003) and Malaysia (Abhayawansa & Abeysekera, 2008;Goh & Lim, 2004).…”
Section: Problem Statementmentioning
confidence: 99%
“…As Ehrlich and Murphy (2007, p. 1) remark: "Human capital theory is one of the most universally accepted concepts in economics and other social sciences". However, devising even approximate metrics is complex due to its very nature, and it is not surprising that it is generally the least disclosed among the intellectual capital categories as defined by the OECD (Abhayawansa and Abeysekera, 2008). For example, in Finland, human capital-based external reporting has been attributed to only about 20 percent of private companies (Ahonen, 2009;Ahonen and Grö, 2005).…”
Section: Human Capital and Goodwillmentioning
confidence: 99%